2011
DOI: 10.1002/14651858.cd003423.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Antihistamines and/or decongestants for otitis media with effusion (OME) in children

Abstract: Cochrane Database of Systematic Reviews REFERENCES References to studies included in this review Cantekin 1983 {published data only} Cantekin EI, Mandel EM, Bluestone CD, Rockette HE, Paradise JL, Stool SE, et al. Lack of e icacy of a decongestantantihistamine combination for otitis media with e usion ("secretory" otitis media) in children. Results of a doubleblind, randomized trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(26 citation statements)
references
References 53 publications
2
23
0
1
Order By: Relevance
“…Similar to our study, they measured tubal patency in both directions, that is, from the middle ear with equalization tests and through the nose/pharynx with the Valsalva maneuver. However, there are long-term studies in the literature that clinically indicate that any longterm effect of such drops or sprays on tube function is very questionable (6). In concordance with the results of Jensen et al (13), we found that nasal decongestion has a benefit on tube opening if higher pressures are applied in the pharynx.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Similar to our study, they measured tubal patency in both directions, that is, from the middle ear with equalization tests and through the nose/pharynx with the Valsalva maneuver. However, there are long-term studies in the literature that clinically indicate that any longterm effect of such drops or sprays on tube function is very questionable (6). In concordance with the results of Jensen et al (13), we found that nasal decongestion has a benefit on tube opening if higher pressures are applied in the pharynx.…”
Section: Discussionsupporting
confidence: 89%
“…A meta-analysis of the Cochrane database found no benefit but some harm from the use of antihistamines or decongestants alone or in combination in the management of SOM in children (6). This idea has made the use of nasal drops or sprays very commonVat least in Germany.…”
Section: Discussionmentioning
confidence: 99%
“…1,12,34,38,64 Furthermore, these interventions are associated with substantial NHS costs. Antibiotic prescription in primary care is rising progressively again, and has now exceeded the peak in the late 1990s, further driving the development of antibiotic resistance, which may lead to serious infections becoming untreatable.…”
Section: Resultsmentioning
confidence: 99%
“…A meta-analysis of 16 randomized controlled trials demonstrated no significant benefit from antihistamines, decongestants, or combined antihistamines and decongestants versus placebo for treatment of OME [77]. Intranasal corticosteroids did reduce the need for surgery in a double blind study in which autoinflation of the middle ear was also effective, but the combination of the two was less efficacious [78].…”
Section: Multi-morbidities Of Allergic Rhinitismentioning
confidence: 99%